Polarization in Court: a corpus-assisted analysis of the language in the Dobbs v. Jackson ruling - Polina Shvanyukova (Amnis)
This study uses corpus linguistic methods to extract top keywords and analyze concordance lines in the majority and dissenting opinions in the U. S. Supreme Court ruling concerning Dobbs v. Jackson released on 24th June 2022. The combination of a quantitative analysis with manual inspection of selected concordances offers linguistic evidence of a deep ideological divide between the majority and dissenting justices that underpins the reality of partisan judicial decision-making.